The interrelationship between leadership and identity formation in the Corinthian correspondence : a study of 1 Corinthians 1-4 - Sindo, Vuyani Stanley (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.